2018
DOI: 10.7150/jgen.24228
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly of the Burying Beetle Nicrophorus orbicollis (Coleoptera: Silphidae) Transcriptome Across Developmental Stages with Identification of Key Immune Transcripts

Abstract: Burying beetles (Nicrophorus spp.) are among the relatively few insects that provide parental care while not belonging to the eusocial insects such as ants or bees. This behavior incurs energy costs as evidenced by immune deficits and shorter life-spans in reproducing beetles. In the absence of an assembled transcriptome, relatively little is known concerning the molecular biology of these beetles. This work details the assembly and analysis of the Nicrophorus orbicollis transcriptome at multiple developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Through the functional description of a large number of genetic data sets and the analysis of the expression of differential genes, valuable information can be provided for insects control strategies. Recently, transcriptome of developmental stages of various coleopteran insects have been sequenced, including Nicrophorus orbicollis (Won et al, 2018), Hypothenemus hampei (Noriega et al, 2019) and Batocera horsfieldi (Yang et al, 2018). In addition, due to the lack of reference genomes, transcriptome sequencing places higher requirements on sequencing tools (Martin & Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the functional description of a large number of genetic data sets and the analysis of the expression of differential genes, valuable information can be provided for insects control strategies. Recently, transcriptome of developmental stages of various coleopteran insects have been sequenced, including Nicrophorus orbicollis (Won et al, 2018), Hypothenemus hampei (Noriega et al, 2019) and Batocera horsfieldi (Yang et al, 2018). In addition, due to the lack of reference genomes, transcriptome sequencing places higher requirements on sequencing tools (Martin & Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on Cylas formicarius showed that the most important KEGG pathways of DEGs during development were pancreatic secretion, lysosome and metabolic pathways, and these pathways may play important roles in different stages of insect development (Ma et al, 2016). At the same time, through the KEGG analysis of Nicrophorus orbicollis and Hypothenemus hampei at different development stages, the resluts showed that functional pathways are mainly related to carbohydrate metabolism, immune system, signal transduction (Won et al, 2018;Noriega et al, 2019). In this work, the data supported the biological differences between the larval and the pupal development stages of R. ferrugineus, which were mainly enriched in the synthesis and metabolism of substances.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, massive transcriptome data of R. ferrugineus was generated, including 63,801 full-length transcripts with 2,964 bp of average length and 3,547 bp of N50 length. The amount of transcriptome data acquired in red palm weevil was much higher than that in Coleoptera insects with different developmental stages by second-generation sequencing, such as Hypothenemus hampei (average length 1,609.92 bp and N50 length 2,427 bp ) (Noriega et al, 2019), Nicrophorus orbicollis (average length 1,193 bp and N50 length 2,856 bp) (Won et al, 2018), Sclerotia aquatilis (average length 1,394 bp and N50 length 2,666 bp) (Chanchay et al, 2019), and Batocera horsfieldi (average length 1,188 bp and N50 length 3,143 bp) (Yang et al, 2018). Meanwhile, a total of 54,999 (86.20%) among 63,801 transcripts of R. ferrugineus were successfully annotated as known homologous genes using seven databases.…”
Section: Discussionmentioning
confidence: 99%
“…Short-reading transcriptome sequencing has been widely used to describe gene expression levels, and many model organisms and non-model organism transcriptomes were obtained by short-sequence sequencing on a second-generation sequencing platform (Nagalakshmi et al, 2008;Ekblom & Galindo, 2011;Djebali et al, 2012). Recently, the expression analysis of Coleoptera insects at different developmental stages have been studied using the next-generation sequencing method (Won et al, 2018;Chanchay et al, 2019;Noriega et al, 2019). Additionally, the research on transcriptome of R. ferrugineus intestinal microbes showed those microbes in the intestine of larva had profound effects on the immune stimulation and nutritional metabolism (Habineza et al, 2019;Muhammad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Development of hair follicles on a skin appendage with a complex growth cycle is characterized by anagen, catagen, and telogen stages, and many key signaling pathways and genes are involved in their regulation [4][5][6] . According to many studies, the WNT/b-catenin signaling pathway in the dermis may be the first dermal signal [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%